2011
DOI: 10.1002/term.488
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and induction of cementoblast cell proliferation by bioactive glass nanoparticles

Abstract: Cementum is a mineralized tissue that lines the surface of the tooth root enabling attachment of the periodontal ligament to the root and surrounding alveolar bone. Studies examining the mechanisms involved in the formation of root cementum have been hindered by an inability to isolate and culture the cells required for cementum production (cementoblasts). This study isolated and characterized cementoblast cells derived from rat molar periodontal ligament. It was observed that the isolated cells expressed F-Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 41 publications
1
29
0
1
Order By: Relevance
“…16 Another study showed that bioactive glass nanoparticles could induce cementoblast proliferation. 15 In our study, NBGs with different sizes support the attachment and proliferation of hMSCs, which demonstrated the cellular biocompatibility of nanoscale BG particles.…”
Section: Discussionmentioning
confidence: 82%
“…16 Another study showed that bioactive glass nanoparticles could induce cementoblast proliferation. 15 In our study, NBGs with different sizes support the attachment and proliferation of hMSCs, which demonstrated the cellular biocompatibility of nanoscale BG particles.…”
Section: Discussionmentioning
confidence: 82%
“…A nearly complete mineralized matrix on the scaffold surfaces was observed on day 21 (Figure C,D). The presence of nBGC in the scaffolds is believed to trigger hDFC biomineralization wherein uniform and completely mineralized matrices were formed . The calcium/phosphate ratio of mineralized chitin–PLGA/nBGC and chitin–PLGA/nBGC/CEMP1 was 1.48 and 1.44 on day 21 as determined by EDS.…”
Section: Resultsmentioning
confidence: 96%
“…According to the revealed results, cytotoxicity could be dependent on the cell type and the ratio of cell number to nanoparticle concentration. Toxicity of BGNs in dental tissue-derived cells such as dental pulp stem cells, odontoblasts, periodontal ligament cells, cementoblasts and gingival fibroblasts was not detected in the low concentration (≤100 μg/mL) and the in vivo study [99][100][101][102] including several clinical cases 5,13,69,74) . However, further detailed researches of BGNs including the long-term study are needed for their safe use 9,13,14) .…”
Section: Biocompatibility Of Bioactive Glass-based Nanocompositesmentioning
confidence: 94%